Implementation of Differentiated Learning in Islamic Religious Education at Darut Taqwa High School - Akbar, Riskon; Fachrudin, Wiwin (At- Ta'lim : Jurnal Pendidikan, 2025)
This study aims to examine the implementation of differentiated learning in Islamic Religious Education (PAI) subjects at Darut Taqwa High School as part of the Mover School program. A descriptive qualitative approach was used with data collection techniques through semi-structured interviews, participatory observation, and documentation review. The research subjects included PAI teachers, students of class X-A, and the principal of SMA Darut Taqwa. The results showed that teachers have implemented differentiation strategies by adjusting learning objectives, processes, and products based on students' interests, abilities, and learning styles. Students are given choices in the form of assignments, such as videos, essays, or infographics, which encourage active participation and learning motivation. Classroom observations show an inclusive, collaborative and adaptive atmosphere, with teachers acting as facilitators. And lesson plans include initial assessments, flexible modules and assessment rubrics that support differentiation. Despite challenges such as time constraints and difficulties in developing fair rubrics, support from the school through training and supervision strengthened implementation. In conclusion, differentiated learning at SMA Darut Taqwa runs systemically and has a positive impact on students' academic and non-academic development.